The Effect of Lexical Predictability on Eye Movements in Reading: Critical Review and Theoretical Interpretation. Issue 8 (August 2015) - Staub, Adrian
Abstract: A word's predictability in its context has a reliable influence on eye movements in reading. This article reviews the extensive literature that has investigated this influence, focusing on several specific empirical issues. These include assessment of cloze probability as the critical measure of predictability, the form of the relationship between predictability and reading time, the distributional effects of predictability, the interaction between predictability and word frequency, and the interaction between predictability and parafoveal preview. On the basis of this review, two theoretical conclusions are proposed. First, predictability effects in reading result from graded activation of potentially many words, as opposed to discrete prediction of a specific word. Second, this activation has the effect of facilitating either very early stages of lexical processing or pre‐lexical processing of visual features or letters.